Potentiality of Solanum torvum as an agent of feminization Anabas testudineus Bloch 1792: a Review - Rahmania, Wanda; Baihaqi, Ahmad Uzair; Heryanto, Heryanto; Handajani, Hany (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Climbing perch (Anabas testudineus) has a high economic value. Females grow faster than males. Sex reversal is one of genetic engineering by manipulating their hormone that is able to change the phenotype from male to female or vice versa.